Tensions and points to educational practices in Professional and Technological Education from the National Conferences on Food and Nutritional Safety (Research, Society and Development, 2022)
This article aimed to apprehend in the construction movement and in the content of the Food and Nutritional Security Policy of Brazil, the approximations, tensions and clues for the "doing" in professional and technological education. We used as main source for data collection the final reports of the National Conferences on Food and Nutrition Security held in 1994, 2004, 2007, 2011 and 2015. In the documents analyzed, the debate around the Food and Nutrition Security was marked by the insurgency of structuring discussions such as food sovereignty, agroecology, the intersectoriality of policies, the solidarity economy and, also, some proposals for the promotion and strengthening of practices related to them in the scope of state action, such as strategies and actions of training and professional qualification articulated with other policies, aimed at specific groups of the field and the city, procedurally breaking the idea of forming for the market. The tensions and clues emerged from the National Conferences on Food and Nutrition Security final reports for professional and technological education still need to be appropriated and enhanced as political and curricular praxis in school institutions, which includes their relationship with the territories in which they are inserted.